Incidence rates of malignancies and hospitalized infectious events in patients with psoriasis with or without treatment and a general population in the U.S.A.: 2005–09. (18th February 2014) - Kimball, A.B.; Schenfeld, J.; Accortt, N.A.; Anthony, M.S.; Rothman, K.J.; Pariser, D.
Abstract : What's already known about this topic? Some evidence shows elevated rates of malignancies and serious infections among psoriasis patients in general but also for those on therapeutic regimens. What does this study add? This study provides evidence that the elevated rates of malignancy and serious infections found in psoriasis patients may be due to biological reasons other than specific treatment modalities. Summary: Background: Rates of malignancies and hospitalized infectious events (HIEs) among psoriasis patients are higher than in the general population, but it is unclear if higher rates are associated with the underlying inflammatory state, treatments or both. Objectives: To assess the incidence of malignancies and HIEs in a healthy US population, a psoriasis population, and four treated psoriasis populations. Methods: Using a US claims database, we identified a general population, a psoriasis cohort, and four treatment cohorts [non‐biologic systemics, etanercept, other TNF blockers (adalimumab, infliximab) and phototherapy] to assess the incidence of lymphomas, nonmelanoma skin cancer (NMSC), all malignancies (excluding NMSC), and HIEs, standardized for age and sex. Results: Among 40 987 patients with psoriasis, 11% were prescribed non‐biologics, 15% etanercept, 6% other TNF blockers and 11% phototherapy. For all cancers, the psoriasis population rate (114/10 000 person‐years) was 20% greater than the rate found in the general population (95/10 000 person‐years). For NMSC, the psoriasis population rate (129/10 000 person‐years) was 65% greater than the general population rate (78/10 000 person‐years). The incidence rate for each treatment modality was lower than the overall psoriasis cohort, except for phototherapy. There was little difference in the rates of lymphomas. NMSC rates were higher among patients treated with phototherapy. HIE rates ranged from 165/10 000 person‐years for the phototherapy group to 262/10 000 person‐years for the other anti‐TNF group. Conclusions: Patients with psoriasis appear to have higher rates of malignancy and HIE than the general population, with little difference in rates between the treatment methods, except for a higher rate of cancer among those receiving phototherapy.